2014
DOI: 10.3140/bull.geosci.1450
|View full text |Cite
|
Sign up to set email alerts
|

The largest Lower Devonian placoderm - Antineosteus rufus sp. nov. from the Barrandian area (Czech Republic)

Abstract: Antineosteus rufus sp. nov. from the upper Emsian of the Czech Republic is described based on two fragments of large dermal plates discovered in the Suchomasty Limestone. The original length of the animal is inferred to have exceeded that of Tityosteus rieversae -the largest Lower Devonian placoderm recorded so far. The occurrence of A. rufus in the Prague Basin is consistent with other giant homostiids in several areas. These animals were apparently adapted to plankton-feeding, although they appeared in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Previous references to the size of D. terrelli are not based on quantitative approaches ( Denison, 1978 ; Frickhinger, 1995 ; Anderson & Westneat, 2007 ; Anderson & Westneat, 2009 ; Albert, Johnson & Knouft, 2009 ; Carr, 2010 ; Long, 2010 ) and some of them are probably overestimates (e.g., 10 m in Anderson & Westneat, 2009 ). Size estimations of other big placoderms have been founded on corporal proportions of Coccosteus , extrapolating the ratio between some shield measurements and total body length calculated in complete specimens of this species (e.g., Gross, 1960 ; Young, 2005 ; Vaškaninová & Kraft, 2014 ). However, the reliability of such approximations should be questioned since the obtained estimates are too far from the usual range of lengths of Coccosteus cuspidatus (one order of magnitude higher) and the presence of allometry has been documented many times in some shield plates of different species (e.g., Werdelin & Long, 1986 ; Zhu & Janvier, 1996 ; Trinajstic & McNamara, 1999 ; Trinajstic & Hazelton, 2007 ; Olive et al, 2014 ), including C. cuspidatus itself ( Miles & Westoll, 1968 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous references to the size of D. terrelli are not based on quantitative approaches ( Denison, 1978 ; Frickhinger, 1995 ; Anderson & Westneat, 2007 ; Anderson & Westneat, 2009 ; Albert, Johnson & Knouft, 2009 ; Carr, 2010 ; Long, 2010 ) and some of them are probably overestimates (e.g., 10 m in Anderson & Westneat, 2009 ). Size estimations of other big placoderms have been founded on corporal proportions of Coccosteus , extrapolating the ratio between some shield measurements and total body length calculated in complete specimens of this species (e.g., Gross, 1960 ; Young, 2005 ; Vaškaninová & Kraft, 2014 ). However, the reliability of such approximations should be questioned since the obtained estimates are too far from the usual range of lengths of Coccosteus cuspidatus (one order of magnitude higher) and the presence of allometry has been documented many times in some shield plates of different species (e.g., Werdelin & Long, 1986 ; Zhu & Janvier, 1996 ; Trinajstic & McNamara, 1999 ; Trinajstic & Hazelton, 2007 ; Olive et al, 2014 ), including C. cuspidatus itself ( Miles & Westoll, 1968 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tens of short reports and taxonomic studies concerning the fauna of the Suchomasty Limestone by these and other authors do exist, some of them cited in these monographs. In addition to the very diverse invertebrate groups, including stratigraphically important goniatites (Chlupáč & Turek 1983) and tentaculitoids (Ferrová et al 2012), remains of a placoderm were observed in the Suchomasty Limestone (Vaškaninová & Kraft 2014).…”
mentioning
confidence: 99%
“…Some of them, including the largest species known from the Prague Basin (which has been estimated to exceed 3 m in length), are considered planctivorous (Vaškaninová & Kraft 2014). Other feeding habits cannot be excluded especially in small forms.…”
Section: Discussionmentioning
confidence: 99%